Effect of Substrate Orientation on the Growth of Germanium Oxide in Dry Oxygen Ambience - Sahari, S.K.; Abdul Halim, N.A.; Muhammad, K.; Sawawi, M.; Hamzah, A.A.; Yeop Majlis, B. (IOP Publishing Ltd, 2017)
The present investigation deals with the effect of substrate orientation effect on the growth of thermally oxidized Ge. The thermal oxidation was performed at temperature between 375 and 550°C in dry oxygen ambient under atmospheric pressure. The thickness of thermally oxidized Ge films was measured by spectroscopic ellipsometry and the chemical bonding structures were characterized by using x-ray photoelectron spectroscopy (XPS). No orientation dependence was observed for the oxidation at temperature of 375°C while for oxidation at 490 and 550°C, Ge oxidation and GeO desorption rate of (100) orientation yield higher rate than (111). The larger atomic space of (100) orientation explains the higher oxidation and desorption rate at Ge surface.